The Relationship Between Job Stress And Employee Turnover Intention - Chin, Pei Jhen (Universiti Malaysia Sarawak (UNIMAS), 2020)
The focus on this study is on determine the relationship between job stresses (work overload, role conflict and role ambiguity) and employee turnover intention. This research was done by using quantitative method where the data were collected by using questionnaires as the instrument. The data was collected from 50 samples in one of the manufacturing company in Kuching, Sarawak. Then, the data were analysed by using descriptive and inferential statistics. Besides that, Pearson Correlation test was used to measure the relationships between the independent variables and dependent variables. The findings have shown that there is a significant relationship between job stress and employee turnover intention. It was also found that role conflict is the most dominant factor affecting the employee turnover intention. Last but not least, the researcher has recommended a focus on the study that may guide the organizations and future researches.